Lady Caroline Lamb : a free spirit - Fraser, Antonia, 1932- (Pegasus Books, 2023)
"The vivid and dramatic life of Lady Caroline Lamb, whose scandalous love affair with Lord Byron overshadowed her own creativity and desire to break free from society's constraints."--Amazon.com.